Indonesian Grain Production Forecasting, Moving Average Method, and Exponential Smoothing - Miratul Haya; Dadang Sukandar (AGRITROPICA : Journal of Agricultural Sciences, 2023)
National food security requires grain for food adequacy, which is then processed into rice as a cereal product, one of the most dominant food commodities for the majority of Indonesian people. The analysis of the ratio normative consumption per capita to cereal production shows that 39.66% of districts in Indonesia experience a deficit in food availability, partly due to population growth which an increase has not matched in cereal production. The purpose of this research is to perform forecasting on the amount of grain production as a reference in formulating a strategy for supplying grain to the population to fulfil the staple food consumption needs of the Indonesian population. This research method uses secondary data on grain production in Indonesia with a range of 2000-2021, and forecasting is carried out until 2024. The data source comes from the Central Statistics Agency (BPS), and data processing uses SPSS (Statistical Package for Social Science). Forecasting techniques use four methods: simple moving average, weight moving average, exponential smoothing and double exponential smoothing. Forecasting results for grain production in 2000-2024 were below actual production, and the peak of production increase occurred in 2017 and then decreased production until forecasting in 2024. The lowest values ​​for MAD, MSE and MAPE were for forecasting results using the WMA method.